Delignification of Palm-press Fibre by White-rot Fungi for Enzymic Saccharification of Cellulose - Chow Chin, Tong; Saw Lee, Chew; Wahab, Mohd. Noor (Universiti Putra Malaysia Press, 1993)
Palm-press fibres were inoculated with fungal mycelium of ten different isolates of white rotfungi namely: Pleurotus sajor-caju I, II and III; Pleurotus florida; Lentinula edodes I, II, III, IV and Vand Ganoderma lucidum. The inoculated fibres were incubated for a period ofup to three months. Of the fungi tested, Pleurotus sajor-caju I, III and P. florida were found to be the best lignin degraders, decreasing the lignin content by as much as 35 %. This corresponded to an increase of 21 % in the digestibility of the fibres. Lignin showed the largest proportionate loss during the growth of these fungi; cellulose and hemicellulose showed the lowest loss for incubation of up to two months. Degradation of hemicellulose seemed to take place later than lignin and cellulose. Some isolates ofL. edodes preferably attacked the lignin component while leaving the cellulose and hemicellulose untouched; its rate of degradation however, was slower than Pleurotus spp. G. lucidum was a poor lignin degrader and under the present conditions preferred to utilise hemicellulose rather than cellulose for growth.